Analisis Implementasi Pembelajaran Tematik Jarak Jauh di Sekolah Dasar pada Masa Pademic Covid-19 - Nasia Azizah; Tri Suryaningsih (Elementar : Jurnal Pendidikan Dasar, 2021)
The aim to find out from this research: (1) Lesson Planning for Online Thematic Subject for Class I at MI Pembangunan UIN Jakarta. (2) Implementation of Online Thematic Subjects Class I at MI Pembangunan UIN Jakarta. (3) Evaluation of Implementation Online Thematic Learning Class I at MI Pembangunan UIN Jakarta. The research method used I this research is descriptive qualitative using data collection techniques namely observation, interviews, and disumentation. The results obtained indicate that the Analisysis Implemnentation of the Online Thematic subject  Class I at MI Pembangunan UIN Jakarta at the planning stage of online thematic learning, a set of activities has been arranged such as interactive power points and learning videos the prepartion of simple lesoon plans before conductnig the onlie learing prosess according to has met the 2013 curriculum standrads which emphasize the scientific approach and madrasah curriculum guidelines during the pandemic issued by the Direct General of Islamic Education,No.2791. At the Implementation stage of learning shows that teachers are able to carry out thematic learning whit a scientific approach and pay attention to the condition of students. At the Evaluation stage of learning outcomes, teacher can carry out good assessements in various aspescts including the assessments that became the standard for 2013 evaluation and assessement of learning outcomesin the emergency period.. Keywords : Implementation, Online Thematic Learning, Pandemic Covid 19.